Capgras Syndrome: In the Conscious and the Unconscious Mind: A Case Report. Issue 12 (December 2022) - Chaudhry, Serena; Weiss, Ashley; Surdis, Costandino; Garrett, Michael
Abstract: We report the successful psychotherapy and medical treatment of a patient with an atypical presentation of Capgras syndrome, in which the patient not only believed that his parents were impostors but also believed that the entirety of what others would consider consensual reality was in fact an impostor. He insisted that a complex delusional world in which he wished to reside was authentic reality. His delusions of misidentification waxed and waned in response to discernable social stressors, and at times, he seemed to have conscious insight into the delusional nature of his beliefs. This case raises questions about whether Capgras should be considered a stand-alone diagnosis or whether it should be placed within a wider spectrum of psychotic disorders. Excepting our current report, although there are numerous reports of the resolution of Capgras after treatment with neuroleptics, we are unaware of descriptions in the literature of the successful treatment of medication-resistant Capgras with a combination of individual psychotherapy and pharmacological management.